Dialectical Intersections of Islamic Legal Normativity and Local Wisdom in the Construction of Ihdād Practices - Soim, Soim; Muhibbin, Moh.; Jannah, Shofiatul (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This research aims to analyze the implementation of ihdad practices in Separah Village, Bangkalan, within the framework of Islamic law and its interaction with local culture ('urf). The main focus of the study is to examine the extent to which customary norms dominate the implementation of ihdad and how this influences religious understanding, gender justice, and the literacy of widowed women in traditional society regarding women's jurisprudence. The method used is a qualitative, case-study approach. Data was obtained through in-depth interviews with widows, religious figures, and village officials, as well as participant observation of social practices related to ihdad. The analysis was conducted descriptively-interpretatively, using data reduction, categorization, and narrative interpretation to uncover the cultural and legal meanings present in the practice. The research results indicate that the implementation of ihdad is more controlled by customary norms than by religious understanding. Women's fiqh literacy is considered low, and the role of religious figures tends to be passive. Ihdad is understood as a social obligation, not merely a spiritual act of worship, thus becoming an instrument of control over women. This research recommends Islamic legal education based on local culture as a solution.